Exosomes of human placenta-derived mesenchymal stem cells stimulate angiogenesis - Motohiro Komaki; Yuri Numata; Chikako Morioka; Izumi Honda; Masayuki Tooi; Naoki Yokoyama; Hirohito Ayame; Kengo Iwasaki; Atsuko Taki; Noriko Oshima; Ikuo Morita (Stem Cell Research & Therapy, 2017)
Abstract Background The therapeutic potential of mesenchymal stem cells (MSCs) may be attributed partly to humoral factors such as growth factors, cytokines, and chemokines. Human term placental tissue-derived MSCs (PlaMSCs), or conditioned medium left over from cultures of these cells, have been reported to enhance angiogenesis. Recently, the exosome, which can transport a diverse suite of macromolecules, has gained attention as a novel intercellular communication tool. However, the potential role of the exosome in PlaMSC therapeutic action is not well understood. The purpose of this study was to evaluate PlaMSC-derived exosome angiogenesis promotion in vitro and in vivo. Methods MSCs were isolated from human term placental tissue by enzymatic digestion. Conditioned medium was collected after 48-h incubation in serum-free medium (PlaMSC-CM). Angiogenic factors present in PlaMSC-CM were screened by a growth factor array. Exosomes were prepared by ultracentrifugation of PlaMSC-CM, and confirmed by transmission electron microscopy, dynamic light scattering, and western blot analyses. The proangiogenic activity of PlaMSC-derived exosomes (PlaMSC-exo) was assessed using an endothelial tube formation assay, a cell migration assay, and reverse transcription-PCR analysis. The in-vivo angiogenic activity of PlaMSC-exo was evaluated using a murine auricle ischemic injury model. Results PlaMSC-CM contained both angiogenic and angiostatic factors, which enhanced endothelial tube formation. PlaMSC-exo were incorporated into endothelial cells; these exosomes stimulated both endothelial tube formation and migration, and enhanced angiogenesis-related gene expression. Laser Doppler blood flow analysis showed that PlaMSC-exo infusion also enhanced angiogenesis in an in-vivo murine auricle ischemic injury model. Conclusions PlaMSC-exo enhanced angiogenesis in vitro and in vivo, suggesting that exosomes play a role in the proangiogenic activity of PlaMSCs. PlaMSC-exo may be a novel therapeutic approach for treating ischemic diseases.